'Alive by default': An exploration of Velleman's unfair burdens argument against state sanctioned euthanasia. (2nd October 2019) - Symons, Xavier; Chua, Reginald
Abstract: In this article we critically evaluate an argument against state‐sanctioned euthanasia made by David Velleman in his 1992 paper 'Against the right to die'. In that article, Velleman argues that legalizing euthanasia is morally problematic as it will deprive eligible patients of the opportunity of staying 'alive by default'. That is to say, those patients who are rendered eligible for euthanasia as a result of legislative reform will face the burden of having to justify their continued existence to their epistemic peers if they are to be perceived as 'reasonable'. We discuss potential criticisms that could be made of the argument, and consider how a defender of the view might respond. Velleman's argument is particularly interesting as it is a consequentialist argument against state‐sanctioned euthanasia, challenging the many consequentialist arguments that have been made in favour of legalizing the procedure. We conclude by suggesting that further research on the question of unfair burdens is important to adequately evaluating the potential harms of legalizing euthanasia for patients at the end of life.